Emerging Role of Diet and Microbiota Interactions in Neuroinflammation - Janakiraman, Mathangi; Krishnamoorthy, Gurumoorthy (Frontiers in Immunology, 2018)
Commensal gut microbiota exerts multifarious effects on intestinal and extra-intestinal immune homeostasis. A disruption in the microbial composition of the gut has been associated with many neurological disorders with inflammatory components. Here we review known associations between gut microbiota and neurological disorders. Further we highlight the emerging role of diet and microbiota interrelationship in regulating neuroinflammation.